2021
DOI: 10.3390/ijerph18073750
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Dental Checkups and Unmet Dental Care Needs: An Examination of Cross-Sectional Data from the Seventh Korea National Health and Nutrition Examination Survey (2016–2018)

Abstract: To identify gender- and age-related associations between adult dental checkups and unmet dental care needs, we analyzed data of 14,000 participants, from the Seventh Korea National Health and Nutrition Examination Survey (2016–2018). Data were collected via self-report questionnaires and interviews. The complex sample chi-square test and multiple logistic regression analysis indicated that 31.7% of participants had unmet dental care needs. Within the previous 12 months, 56.5% did not undertake dental checkups,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The result of this study was somewhat high, with 57.4% of individuals responding that they had not undergone an oral examination in the last year . In addition, in a study on dental check-ups and unmet dental care needs based on the 7 th KNHANES [47], 31.7% reported unmet dental care needs, while 56.5% of people did not undergo oral check-ups. Thus, the proportions of those who did not use dental treatment and of those who did not undergo oral examination were higher among inmates in the present study than among adults in the general Korean population.…”
Section: Discussionmentioning
confidence: 99%
“…The result of this study was somewhat high, with 57.4% of individuals responding that they had not undergone an oral examination in the last year . In addition, in a study on dental check-ups and unmet dental care needs based on the 7 th KNHANES [47], 31.7% reported unmet dental care needs, while 56.5% of people did not undergo oral check-ups. Thus, the proportions of those who did not use dental treatment and of those who did not undergo oral examination were higher among inmates in the present study than among adults in the general Korean population.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the results of several previous studies that reported that periodontal disease prevalence differs owing to differences in access to dental care depending on the socioeconomic level. [21][22][23] Evidently, despite various national efforts to promote oral health, periodontal disease prevalence according to general characteristics remains unimproved.…”
Section: Ta B L E 3 Multiple Logistic Regressionmentioning
confidence: 99%
“…2 Regular dental checkups enable the patients to be guided by the dentists for appropriate oral hygiene measures, correction of faulty oral care habits and for reversal of few of the dental problems. 3 Poor dental care and neglecting the need for dental treatment is a common community health problem. 4 Most of the patients that visit dental clinics and hospitals have already lot of decayed teeth and periodontal and other problems.…”
Section: Introductionmentioning
confidence: 99%
“…Finding these reasons help in developing effective health-policy interventions to optimize the oral health of the population. 3 Currently no study is available to evaluate the attitude of patients in Abha, Saudi Arabia, towards attending dental clinics for routine dental check-ups. In order to address this issue, the present study was carried out to find out multiple reasons for infrequent dental visits by female patients attending dental OPD of King Khalid University, Abha, Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%